Popular Art - Painting in Zaïre : Art Bodo - Lelo - Moke - Cheri Samba - Syms - Simsimaro. (Kinshasa : Galerie privée Louis van Bever, 1992)
Art Bodo ; Lelo ; Moke ; Cheri Samba ; Syms - Simsimaro
Popular Art - Painting in Zaïre : Art Bodo - Lelo - Moke - Cheri Samba - Syms - Simsimaro, Hotel Maastricht, 28 June - 27 August 1992
boek
Keywords: Afrika; Zaïre